"We Just Thought We Were Superhuman": An Oral History of Noise and Piecework in Paisley's Thread Mills. (1st November 2020) - Burns, William
Abstract : Paisley, in the West of Scotland, was once the world capital of industrial thread making. Existing scholarship on the thread works has focused on the "great men" of the mill-owning Coats and Clark families, neglecting the experience of female factory workers. This article explores the hidden history of the experience of work-induced illness and disability over the long term, from the perspective of women who worked in Paisley's thread mills. It draws upon extant oral history interviews and 13 new interviews with former millworkers. There is a particular focus on two work–health interactions: first, repeated exposure to the constant roar of machinery, which resulted in hearing loss; second, piecework – compelling women to work at speed and to engage in repetitive movements and awkward postures in order to increase their earnings – which had a debilitating effect on their joints and limbs in later life. This article examines oral testimony of the long-term health implications for Paisley's female thread workers and reveals that women engaged in risky work practices not only as victims of the industrial process but with agency in their desire to earn increased wages. This agency was framed within the inevitability of the absorption of risk, and curtailed by mechanical, social and financial factors.